Sources of inequality in selected MENA countries - DOĞRUEL, FATMA (My University, 2012)
The paper deals with income inequality in the selected MENA countries focusing on the dynamics of domestic wage differentiations. The main aim is to identify the sources of inequalities. GDP per capita, share of manufacturing sector, urban share of population, gender participation in the labor force, education and openness may be possible factors. The paper analyzes pay inequalities using a panel regression model where the Theil index is used as the dependent variable. The results show that GDP per capita and female labor force participation have positive (increasing) effects, and openness has a negative (decreasing) effect on pay inequalities in these countries. © 2012 .
Keywords: Inequality measures; MENA countries; Pay inequality; Sources of inequality; Theil index; Turkey